2005
DOI: 10.2337/diacare.28.6.1303
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Kidney Graft Survival, Hypertrophy, and Vascular Function in End-Stage Renal Disease Type 1 Diabetic Kidney-Transplanted Patients

Abstract: OBJECTIVE -Diabetes, hypertension, infections, and nephrotoxicity of certain immunosuppressive drugs (i.e., calcineurin inhibitors) can reduce functional survival of the kidney graft. Our aim was to evaluate survival, hypertrophy, and vascular function of the kidney graft in end-stage renal disease (ESRD) type 1 diabetic patients after transplant. RESEARCH DESIGN AND METHODS -The study population consisted of 234 ESRD type 1 diabetic patients who underwent kidney-pancreas (KP; 166 patients), successful kidney-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 44 publications
2
57
0
6
Order By: Relevance
“…However, immunosuppression consisted of only one potentially nephrotoxic drug (i.e., cyclosporine), and insulin independence was prolonged for a decade. In patients who underwent simultaneous pancreas-kidney or islet-kidney transplantation, improved cumulative survival, kidney graft size, and function were reported in the group with a functioning pancreas or islets (9). Furthermore, insulin independence was not required for a positive effect on kidney function (8), supporting the EDIC finding that patients with type 1 diabetes with residual C-peptide function have a lower risk of diabetic nephropathy (2).…”
Section: Diabetes Who Received Islet Transplantation Alone and The Edsupporting
confidence: 72%
See 1 more Smart Citation
“…However, immunosuppression consisted of only one potentially nephrotoxic drug (i.e., cyclosporine), and insulin independence was prolonged for a decade. In patients who underwent simultaneous pancreas-kidney or islet-kidney transplantation, improved cumulative survival, kidney graft size, and function were reported in the group with a functioning pancreas or islets (9). Furthermore, insulin independence was not required for a positive effect on kidney function (8), supporting the EDIC finding that patients with type 1 diabetes with residual C-peptide function have a lower risk of diabetic nephropathy (2).…”
Section: Diabetes Who Received Islet Transplantation Alone and The Edsupporting
confidence: 72%
“…In patients with type 1 diabetes, pancreas or islet transplantation has improved kidney graft survival (8,9), whereas the positive impact of pancreas transplantation on the native kidney has been counterbalanced by the nephrotoxicity of immunosuppressants, namely calcineurin inhibitors (10,11).…”
mentioning
confidence: 99%
“…*P!0.05, **P!0.01 vs DN group. (Fiorina et al 2003(Fiorina et al , 2005. Recent studies have indicated that C-peptide produced by islet cells might help to prevent and treat diabetic microvascular lesions (Cotter et al 2003, Forst & Kunt 2004, Hills et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a positive impact of islet transplantation on the progression of diabetes complications has been reported. Although, most of the studies showing reduced complications were small-scale and nonrandomized [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%